Reforming Asset Recovery Work Procedures for Effective and Just Corruption Handling - R. Narendra Jatna; Titin Herawati Utara; Bobur Baxtishodovich Sobirov; Suci Wijayanti (Jurnal Justice Dialectical, 2025)
The current institutional structure of the Asset Recovery Center (Pusat Pemulihan Aset/PPA) under the Indonesian Attorney General’s Office poses significant challenges in the effective recovery of assets from criminal acts, particularly corruption. The PPA’s position under the Junior Attorney General for Administration limits its strategic function, decision-making authority, fiscal autonomy, and coordination across prosecutorial levels. This article proposes a new institutional model by transforming the PPA into an independent Asset Recovery Agency (Badan Pemulihan Aset/BPA) to enhance efficiency, legal responsiveness, and institutional performance in asset recovery. This study employs a normative legal approach alongside theoretical perspectives on institutional effectiveness, bureaucratic rationality (Max Weber), and modern organizational systems. The analysis is descriptive-qualitative, based on legal and organizational frameworks. The study finds that reconstructing the PPA into a level-one agency (Eselon I) directly under the Attorney General would strengthen authority, expedite decision-making, and allow for independent budget control. The proposed structure introduces vertical integration with asset recovery units at regional levels and functional specialization through five strategic centers, including transnational cooperation. This model supports faster, transparent, and accountable asset recovery aligned with the principles of good governance and substantive justice.